The Cultural and Artistic Legacy of Oliver Mtukudzi
XVII, 268 p. 2 illus.
Keywords: This book delves into a critical and comprehensive analysis of Mtukudzi’s legacy, as an outstanding musician who anchored his music on cultural identity specifically through the artistic manipulation of language. As a cultural worker, his remit extended beyond performance. This raised his stature to the levels of such African music icons as Fela Kuti of Nigeria, Salif Keita of Mali and Miriam Makeba/Hugh Masekela of South Africa, all towering giants in African musical performance. This volume examines how Mtukudzi artistically manipulated language to convey a timeless message of cultural identity, fighting for the respect of rights for women, children and all. It unpacks how Mtukudzi subtly uses language to put across political views that speak truth to power, harnessing Zimbabwean language to articulate and promote the nation’s cultural heritage and to advocate for societal development and the promotion of rights of vulnerable groups. The chapters in this volume are a mix of interdisciplinary Zimbabwean scholars of linguistics, performance studies, religion, history, communication and media studies, unravelling Mtukudzi as a fighter for human rights and justice who subtly critiqued political systems and practices. It concludes that Mtukudzi strove to be a cultural worker who used the power of language through music to contribute towards the rehabilitation of a battered African identity. Munyaradzi Nyakudya is Senior Lecturer in the History Heritage and Knowledge Systems Department of the University of Zimbabwe. Bridget Chinouriri is Senior Lecturer in the Creative Media and Communication Department of the University of Zimbabwe. Pauline Mateveke is Senior Lecturer in the Languages Literature and Culture Department of the University of Zimbabwe. Ezra Chitando is Professor of Religious Studies in the Philosophy Religion and Ethics Department of the University of Zimbabwe.